DEVELOPMENT OF MOTORCYCLE TUNE UP TUTORIAL VIDEO MEDIA FOR GRADE X STUDENTS OF MOTORCYCLE TECHNIQUE AND BUSINESS EXPERTISE COMPETENCY AT SMK MUHAMMADIYAH BAWANG - Budiyanto; Ariwibowo, Bayu; Mahendra, Sena; Burhan, Nurul (Universitas Negeri Semarang, 2025)
This study aims to develop learning media in the form of a video tutorial on motorcycle tune-up practices for class X students of Motorcycle Engineering and Business Expertise at SMK Muhammadiyah Bawang. The method used is research and development (R&D) by adapting the Borg & Gall model to the final product trial stage. Data collection was carried out through observation, interviews, expert validation questionnaires, student response questionnaires, and practical skills tests. The results of the study showed that the video tutorial media developed obtained the category